2023
DOI: 10.3390/nu15061404
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3-Supplemented Fat Diet Drives Immune Metabolic Response in Visceral Adipose Tissue by Modulating Gut Microbiota in a Mouse Model of Obesity

Abstract: Obesity is a chronic, relapsing, and multifactorial disease characterized by excessive accumulation of adipose tissue (AT), and is associated with inflammation mainly in white adipose tissue (WAT) and an increase in pro-inflammatory M1 macrophages and other immune cells. This milieu favors the secretion of cytokines and adipokines, contributing to AT dysfunction (ATD) and metabolic dysregulation. Numerous articles link specific changes in the gut microbiota (GM) to the development of obesity and its associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 83 publications
1
8
0
Order By: Relevance
“…Additionally, leukotriene B4 (LTB4) and prostaglandin E2, which exacerbate lung cancer [ [24] , [25] , [26] , [27] ], are upregulated in the lungs. However, isohumulone, which is a peroxisome proliferator-activated receptor gamma (PPARγ) activator [ 28 ], and resolvin (an ω-3 PUFA), one of the specialized pro-resolving mediators (SPMs), which both have anti-cancer effects, were upregulated in the small intestine and colon [ [17] , [18] , [29] , [30] , [31] ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, leukotriene B4 (LTB4) and prostaglandin E2, which exacerbate lung cancer [ [24] , [25] , [26] , [27] ], are upregulated in the lungs. However, isohumulone, which is a peroxisome proliferator-activated receptor gamma (PPARγ) activator [ 28 ], and resolvin (an ω-3 PUFA), one of the specialized pro-resolving mediators (SPMs), which both have anti-cancer effects, were upregulated in the small intestine and colon [ [17] , [18] , [29] , [30] , [31] ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…We have reported that COX 10 KO mouse are typified by decreased white adipose stores, accelerated lipolysis with increased free fatty acid deposition and low leptin levels with decreased food intake 49 . We have since applied lipid and fatty acid ratio imaging to evaluate potential metabolic and enzyme activities that may be responsible for lipid and fatty acid metabolic features in adipose tissue of 50 , obesity 51 , altered gut microbiota 52,53 among other health problems 54,55 . These ratio imaging findings led us to speculate that the diminished ω3 to ω6 ratio arises in COX 10 KO mice from an altered gut microbiota population, supported by unpublished preliminary findings.…”
Section: Targeted Metabolite Ratio Imaging Reports Spatial Enzyme And...mentioning
confidence: 99%
“…PUFAs can also decrease plasma triglycerides together with activities of cholesteryl ester transfer protein (CETP) and hepatic lipase, while enhancing cholesterol efflux capacity of HDL as well as LPL and lecithin-cholesterol acyltransferase (LCAT) activities [17]. In this regard, two recent studies reported that n-3 PUFAs could attenuate high-fat diet-induced hyperlipemia and increase HDL-C levels [21,22].…”
Section: High-density Lipoprotein and Food Intakementioning
confidence: 99%